Lead screening in children presenting to three hospitals in Lebanon. Issue 3 (24th August 2021) - El Zahran, Tharwat; Mostafa, Hala; Hamade, Hani; Al Hariri, Moustafa; Saab, Aed; Tamim, Hani; Tohme, Rasha; Al Hamod, Dany A; Sinno, Durriyah; Sawaya, Rasha Dorothy; Kazzi, Ziad
Abstract : Background: Lead damages most body organs and its effects are most profound in children. In a study in Beirut in 2003, before banning the leaded gasoline, 79% of the participants showed blood lead levels (BLLs) higher than 5 µg/dL. The prevalence of lead exposure in Lebanon after the ban on leaded gasoline has not been studied. This study assessed the BLL in Lebanese children aged 1–6 years. Methods: This cross-sectional study was conducted in three hospitals in Beirut. The children's BLLs were tested, and their caregiver completed a questionnaire to identify subgroups at risk of exposure. Participants were provided with a WHO brochure highlighting the risks of lead. Results: Ninety children with a mean age of 3.5±1.5 years were enrolled in the study and had a mean BLL of 1.1±0.7 µg/dL, with all values being below 5.0 µg/dL, showing a marked decrease in BLL compared with the mean BLL before the ban on leaded gasoline in 2002. Having a father or a mother with a college degree (p=0.01 and p=0.035, respectively) and having a monthly household income greater than $1000 (p=0.021) were associated with significantly lower BLL. Having more rooms at home and residing close to construction sites were associated with a significantly lower BLL (p=0.001 and p=0.026, respectively). Residing in a house aged >40 years and receiving traditional remedies were associated with a significantly higher BLL (p=0.009 and p<0.0001, respectively). Conclusion: BLLs have declined among Lebanese children and this could be attributed to multiple factors including the ban of leaded gasoline. It would be beneficial to conduct a larger study with a nationally representative sample to better characterise the BLL. Abstract : This study in three hospitals in Lebanon studied blood lead levels in 90 children the mean blood lead level was 1.05 μg/dL. All values were below 5.0 μg/dL, a marked decrease compared to before a national ban on leaded gasoline in 2002. The study identified risk factors for higher blood lead levels, including living in a house aged 40 years or more, receiving traditional remedies, and a lower household income.